Strategies for the People's Republic of China's Small and Medium Enterprise Development within the National Innovation System - Tracy Yang; Jamus Jerome Lim; Toshiki Kanamori (Asian Development Bank Institute (ADBI), 2008)
With deregulation and globalization, and the impact of these developments on economies worldwide, it has become necessary for the PRC authorities to consider an approach that would further attune its economic engine toward sustained growth. This paper argues that certain sectors of the economy|in particular, the small and medium enterprise (SME) sector|may play a significant role in terms of any further reforms of the PRC's national innovation system, which in turn could spur continued growth. It highlights how issues such as innovation, research and development, and strategic clustering influence the SME sector, and outlines internal and external conditions that may impact the further development of this sector.
hdl:11540/4178
Keywords: 330; Economic Development; Economic Infrastructure; Economic Policies; Regional Economic Development; Microfinance Programs; Public Finance; Local Financing; Financial Stability; Financial Sector Regulation; Enterprises; Financial aid; Economies in transition; Technologiepolitik; KMU; China